10 Days Vonoprazan -Amoxicillin Dual Therapy Versus Concomitant (Drugs Regimen) for First Line Helicobacter Pylori Eradication - Kainat Latif, Murtaza Ali, Rida Naseer, Binish Anwar, Shafqat Ur Rehman Orakzai, Humaira Rahim (Pakistan Journal of Medical & Health Sciences, 2023)
ABSTRACT Objective: This study was carried out to determine the outcomes of 10 days vonoprazan -amoxicillin dual therapy versus concomitant (drugs regimen) for first line helicobacter pylori eradication. Material and Methods: This multicentre cross-sectional study was carried out at the DHQ hospital Kohat, from January 2023 to June 2023 after taking approval from the ethical committee of institute. Prior to study each participant provided written, informed permission. A total of 394 Individuals whose age was 18 to 70 years old and had H. pylori infection were included. The rate of various regimens based on the PP, modified intention-to-treat (mITT), and intention-to-treat (ITT) analyses. Overall of 3 participants (one hundred and fifty seven individuals in individual group) were anticipated for acceptance. Taking into account a 10% loss of follow-up. For analysis SSPSS Software was used (version 26.0).variables were presented in the form of percentage (%) and frequencies while continuous variable were shown in mean and standard deviation .comparisons were made using Student’s t-test. variables were matched by the Chi-square test. Absolute non-inferiority of the two sets was evaluated using hypothesis testing and derivation of a 2-sided 95% CI. The value of p (0.05) was measured to be statistically significant. Results: A total of 394 patients diagnosed with Helicobacter were included in this study. Out of them 314 were treated through VA-dual and B-quadruple for further ITT analysis. In the vonoprazan -amoxicillin dual treatment the eradication rate of H. pylori was eighty six (95 % CI: 80.6 to 91.4%, 135/ 157) and 88. (95% CI: 83.1 to 93.3%, 134/154), correspondingly. On other hand drugs regimen (B-quadruple) group eradication was 89.2% (95% CI: 84.3%–94.1%, 140/157) and 91.5 (95% CI: 87.1%–95.9%, 140/153) percent. In the same way PP analysis evolved ninety percent (95% CI: 86.0 to95.6%, 128/141) and 91 percent (95% CI: 86.6–96.0%, 126/138) in the vonoprazan -amoxicillin dual therapy and drugs regimen, correspondingly. The percentage adverse effects in concomitant treatment group was much higher (43.9%) while this was less (21.0%) in 10 day VA-dual therapy group. Conclusion: Our study concludes that 10-day VA-dual therapy is effective for H. pylori eradication (90 %) with few adverse effects as compared to concomitant (drugs regimen) treatment. It is a promising cost-effective too. Keywords: vonoprazan -amoxicillin dual therapy, concomitant, Pylori treatment